2011
DOI: 10.1128/jb.05978-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Biochemical Characterization of Sco3487 from Streptomyces coelicolor A3(2), an Exo- and Endo-Type  -Agarase-Producing Neoagarobiose

Abstract: Streptomyces coelicolor can degrade agar, the main cell wall component of red macroalgae, for growth. To constitute a crucial carbon source for bacterial growth, the alternating ␣-(1,3) and ␤-(1,4) linkages between the 3,6-anhydro-L-galactoses and D-galactoses of agar must be hydrolyzed by ␣/␤-agarases. In S. coelicolor, DagA was confirmed to be an endo-type ␤-agarase that degrades agar into neoagarotetraose and neoagarohexaose. Genomic sequencing data of S. coelicolor revealed that Sco3487, annotated as a put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 30 publications
1
43
0
Order By: Relevance
“…Agarolytic activity has also been rarely observed in terrestrial bacteria, such as Paenibacillus (Hosoda et al 2003), Pseudomonas (Song et al 2015, and Streptomyces (Temuujin et al 2012). Here, we reported the isolation of a Gram-positive soil bacterium, Cohnella sp.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Agarolytic activity has also been rarely observed in terrestrial bacteria, such as Paenibacillus (Hosoda et al 2003), Pseudomonas (Song et al 2015, and Streptomyces (Temuujin et al 2012). Here, we reported the isolation of a Gram-positive soil bacterium, Cohnella sp.…”
Section: Introductionmentioning
confidence: 63%
“…The chemical shifts of the anomeric carbon signals in the spectrum were identical to those of a typical pattern for neoagarooligosaccharides (Fu et al 2008;Rochas et al 1986;Temuujin et al 2012).The resonances at 92.360 and 96.182 ppm were signals for the α-and β-anomeric forms of the galactose unit at the reducing end of the neoagarooligosaccharides, respectively. No resonance was detected at 90.8 ppm, which was the characteristic signal of the reducing end of the hydrated form of 3,6-anhydro-L-galactose of the agarooligosaccharides (Fu et al 2008;Rochas et al 1994;Temuujin et al 2012). Thus, the dimer, tetramer, and hexamer agarolytic products were identified as neoagarobiose, neoagarotetraose, and neoagarohexaose, respectively.…”
Section: Mode Of Actionmentioning
confidence: 95%
“…In silico analysis predicted the absence of a signal peptide in Sco3481. When expressed in S. lividans TK24, the protein was present only in the cytosol, quite distinct from the behavior of the two extracellular β-agarases DagA and DagB (Temuujin et al 2011(Temuujin et al , 2012. The purified Sco3481 hydrolyzed neoagarobiose to G and LA and released LA from the non-reducing ends of neoagarotetraose and neoagarohexaose was released in the same way as Aga117F from S. degradans 2-40 (unpublished data).…”
Section: Agar Degradation By Streptomyces Coelicolormentioning
confidence: 75%
“…Biochemical study of mature DagB (83.9 kDa) revealed that it is both an exo-and endo-β-agarase that degrades agarose, neoagarotetraose, and neoagarohexaose into neoagarobiose. In addition, agarose hydrolysis to neoagarobiose was synergistically enhanced by coincubation of the substrate with DagA and DagB, implying that the two enzymes can hydrolyze agarose in a cooperative way (Temuujin et al 2012).…”
Section: Agar Degradation By Streptomyces Coelicolormentioning
confidence: 98%
“…Typically, β-agarases are divided into types I and II, depending on substrate specificity and product profile. Thus, type I cleaves agarose into neoagarotetraose, while the major product of type II is neoagarobiose (Temuujin et al, 2012). Several reports on the identification and characterization of β-agarases have been presented recently, that highlight the topicality of this matter.…”
Section: Agarasesmentioning
confidence: 99%